Implementation of the School's Healthy Canteen in Improving the Quality of Education at SD Negeri Krapyak Wetan Sewon Bantul Yogyakarta - Ainur, Ainur; Subiyantoro, Subiyantoro (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2021)
The canteen is a service that facilitates food and drink for students and other school staff. This study aims to determine and describe the implementation of a healthy canteen and the pattern of organizing a healty school canteen in improving the quality of education at SD Negeri Krapyak Wetan Sewon Bantul Yogyakarta. This study uses a qualitative descriptive approach. Data collection techniques used were observation, interviews, documentation. Data analysis in this study used three stages, namely data reduction, data exposure, drawing conclusions and verification. The results showed that the implementation was carried out based on the obligation of schools to provide a healthy canteen, fulfillment of daily nutrition, internal management of the school and management by third parties